Survey of Energy Finance on the Corporate World - Althaqeb, Saud (International Journal of Energy Economics and Policy, 2017)
This literature review surveys some of the main topics regarding energy finance in the field of empirical corporate finance. The basic goal is to conduct literature surveys on some of the major studies in the field that focus on energy finance. The primary focus is on corporate governance, capital structure, risk management, and hedging in relation to energy finance. This review will study the effect of accounting differences in corporate finance, IPOs, and mergers and acquisitions. This is done by summarising some of the existing literature in these areas with regard to energy finance in order to synthesize this research and examine the impact on corporate financial decision making. Keywords: energy finance; corporate; corporate governance, capital structure, risk management IPO and mergers and acquisitions. JEL Classifications: F30, F39